Object and method in Immanuel Kat’s philosophy - Noras, Andrzej J. (Folia Philosophica, 2002)
Kant’s reflection on the essence of transcendentalism was accompanied not only by his awareness of the novelty of his stance, but also by a methodological awareness that manifested itself in his preoccupation with the method and idea of philosophy. This preoccupation can be seen in his taking up such problems with great prudence, and avoiding ultimate solutions. Kant, being fully aware of the novelty of his stance, did not want to close the discussion on the idea and methods of philosophy, the discussion that has been going on since his time to the present day (in the 20th c. particularly within neo-Kantianism and Phenomenology).